Synthesis and Growth Promoting Effects of Some Newly Synthesized Chlorosubstituted Heterocycles on Agricultural Crop Plants - R. Maurya, Mithilesh; V. Parhate, Vandana; Tidke, J.A.; Rajput, P.R. (Asian Journal of Chemistry, 2010)
In the present study, the synthesis and growth promoting effects of 4-aroylpyrazolines, pyrazoles, isoxazolines and isoxazoles on cultivated agricultural crop plants, namely, Triticum aestivum (wheat). Sorghum vulgare (jowar). Cicer arietinum (gram) and Phaseolus vulgaris (Rajma) were undertaken.